P84 Optimising hand trauma care at a Major Trauma Centre (MTC) during the COVID-19 pandemic. (8th April 2021) - Khajuria, Apoorva; Jones, Matthew
Abstract: Introduction: This study evaluates the management of hand injuries during COVID-19 following the prompt implementation of the BOA guidelines; reconfiguration of hand services and implementation of the 'one-stop' model. Methods: 285 cases OVER A 1-MONTH PERIOD were RETROSPECTIVELY reviewed to evaluate the effectiveness of managing patients using the 'one-stop' model and the new Urgent Treatment Centre (UTC). Results: 277 patients were included in the study. During Covid-19, operative cases fell by 62%. 86.3% (239/277) of cases were managed in the UTC; 54.4% (130/239) required conservative management and 45.6% (109/239) required minor procedures (in UTC). REMOVABLE SPLINT USE was optimized through design of 'softcasts' for non-operative management of distal radius fractures. A patient education video: 'softcast removal at home' was created and in cases requiring sutures, 95.1% (39/41) were absorbable, thereby avoiding COVID-19 exposure for follow-up. Only 50.5% (140/277) of patients had formal follow-up arranged and patient information follow-up cards were developed. Conclusion: The one-stop model prevents delay in definitive treatment, allows effective initial treatment, and minimizes the need for face-to-face follow up. In light of a possible second wave of COVID-19 cases, this new model should be considered for implementation by all hand's units for the foreseeable future.